Nonunique Fixed Point Results via Kannan F-Contraction on Quasi-Partial b-Metric Space - Pragati Gautam; Santosh Kumar; Swapnil Verma; Gauri Gupta (Journal of Function Spaces)
This paper is aimed at acquainting with a new Kannan F-expanding type mapping by the approach of Wardowski in the complete metric space. We establish some fixed point results for Kannan F-expanding type mapping and F-contractive type mappings which satisfy F-contraction conditions. Additionally, some new results are given which generalize several results present in the literature. Moreover, some applications and examples are provided to show the practicality of our results.